2012
DOI: 10.7166/21-2-45
|View full text |Cite
|
Sign up to set email alerts
|

The Visibility of Engineering Research in South Africa, 1975-2005

Abstract: Engineering as a branch of science has a crucial role in the growth of the economy. The growth and development of engineering is therefore highly relevant. One way to understand this is to examine the characteristics of the scientific knowledge produced in the field of engineering. Drawing on the publications in engineering from the ISI Web of Science over the last three decades, this paper looks at the visibility and importance of engineering research in South Africa. The visibility of research publications i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 24 publications
(19 reference statements)
0
3
0
Order By: Relevance
“…The model of scientific collaboration in South Africa that has emerged from a series of studies conducted in the last few years [41][42][43][44][45][46][47][48][49][50] is unique in several respects and can perhaps offer some lessons for other countries. In South Africa, scientific collaboration is an accepted practice among scientists, supported by the government, higher education institutions, research institutes, industry, the private sector and individual scientists.…”
Section: The South African Modelmentioning
confidence: 99%
“…The model of scientific collaboration in South Africa that has emerged from a series of studies conducted in the last few years [41][42][43][44][45][46][47][48][49][50] is unique in several respects and can perhaps offer some lessons for other countries. In South Africa, scientific collaboration is an accepted practice among scientists, supported by the government, higher education institutions, research institutes, industry, the private sector and individual scientists.…”
Section: The South African Modelmentioning
confidence: 99%
“…Sooryamoorthy [9], making a pioneering attempt, provides a bibliometric analysis of the trends and patterns of South African engineering research since 1975. Another study on the visibility of engineering publications, which appeared in the South African Journal of Industrial Engineering, has examined the visibility of South African engineering research as measured by the number of citations that engineering publications received [8]. This study showed how the visibility of South African engineering research is determined by certain key variables.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have investigated trends in engineering research, as shown in the publications stored in different databases for varying periods of time [3][4][5][6][7][8][9]. Some have explored the collaborative dimensions hidden in such scientific publications [10][11][12].…”
Section: Introductionmentioning
confidence: 99%